2014
DOI: 10.13102/sociobiology.v61i2.145-154
|View full text |Cite
|
Sign up to set email alerts
|

Richness of Termites and Ants in the State of Rio Grande do Sul, Southern Brazil

Abstract: Previous studies on the effects of environmental factors, such as altitude, latitude, temperature, deforestation, forest fragmentation, fire, and flood on the community structure of termites and ants were conducted in various regions of Brazil; few of them were carried out in the southernmost Brazilian state of Rio Grande do Sul. Here we describe termites and ants diversity at different sites along the four geomorphologic units of this state. We recorded 16 taxa of termites, of which three are new state record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Discussion This study represents the first attempt to characterize the ant fauna from South Brazilian grasslands reaching sites distributed in two biomes sampled long-term in two target microhabitats. The survey presents the highest ant richness already recorded for these ecosystems, and also adds two new ant species records to Rio Grande do Sul state (based on Diehl et al, 2014 and 1929(Ant Maps, 2016Ant Wiki, 2016). Furthermore, a new species was found (Acanthoponera sp.…”
Section: Resultsmentioning
confidence: 99%
“…Discussion This study represents the first attempt to characterize the ant fauna from South Brazilian grasslands reaching sites distributed in two biomes sampled long-term in two target microhabitats. The survey presents the highest ant richness already recorded for these ecosystems, and also adds two new ant species records to Rio Grande do Sul state (based on Diehl et al, 2014 and 1929(Ant Maps, 2016Ant Wiki, 2016). Furthermore, a new species was found (Acanthoponera sp.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Diehl et al (2014) listed a total richness of 127 ant species in the inventory of Rio Grande do Sul state, fewer than the total recorded in PEG.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, only a few number of ant surveys were conducted in the Brazilian southern grasslands, all in the state of Rio Grande do Sul (Diehl et al, 2005;Diehl et al, 2014;Albuquerque & Diehl, 2009;Rosado et al, 2012). Diehl et al (2005) found 60 species in a sampling expedition to three habitats within Itapuã State Park, a coastal area with sandy soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less works called attention to animal species, which also occur as endemic in grasslands around the world (Bond & Parr 2010). Thus, surveys of arthropods richness and abundance can provide interesting data about the value of such grasslands for the conservation of animal diversity (Albuquerque & Diehl 2009, Azcárate & Peco 2012, Rosado et al 2012, Diehl et al 2014.…”
Section: Introductionmentioning
confidence: 99%